Semiotic analysis of gender bias in news coverage of Reog Ponorogo art - Fingky Ayu Puspitasari; Ayub Dwi Anggoro (Jurnal Studi Komunikasi, 2024)
The focus of this research is to analyse the semiotic meaning conceptualised by Roland Barthes, which includes denotative and connotative meanings. This also delves into the myths constructed by the media-related representation of gender switching in Jathil Dancers in Reog Ponorogo and its relationship with the Media Coverage of Gemblak. Researchers extracted data by collecting news from mass media portals that discussed Gemblak Ponorogo. The results showed that mass media significantly maintains people's views on culture and tradition. In Roland Barthes' semiotic analysis, some media employ negative language that can influence a negative view of Gemblak. The media, with its point of view, news sources, and characterisation of those in the news, can significantly affect people's perceptions, and it continues to maintain these assumptions until now.